The East moves West : India, China, and Asia's growing presence in the Middle East - Kemp, Geoffrey (Brookings Institution Press, 2010)
"Details the growing interdependence of the Middle East and Asia and its likely ramifications. Particular attention is given to India and China, which have a strong interest in trade--especially in oil and natural gas--with the Middle East and Central Asia"--Provided by publisher